Dividend Policy Changes In The Pre-, Mid-, And Post-financial Crisis: Evidence From The Nigerian Stock Market - Abdulkadir, Rihanat Idowu; Hiau Abdullah, Nur Adiana; Wong , Woei Chyuan (Asian Academy of Management (AAM), 2015)
This paper examines the impact of the global financial crisis on Nigerian listed firms' dividend policies. Our findings indicate that firms adjust their dividend policies in a manner consistent with the need to preserve financial flexibility and mitigate goingconcern risks during the crisis period. Specifically, highly leveraged firms and firms with low cash flows are more likely to omit dividend payments during the crisis. Moreover, the negative effects of foreign ownership on dividend payments during the pre-crisis are muted during the crisis. This suggests that the tax-induced clientele effect became irrelevant as cash dividends became the first order of business for foreign investors during the crisis. In the same vein, prevailing investor demand for cash dividends exerts a positive influence on firms' probability to increase dividends during the crisis, implying that markets attach a high valuation to firms that are able to pay during the crisis period. We also find support for past dividends as a reference point for current dividend decisions in both the crisis and non-crisis periods, although the relation is weakened during the crisis. This implies that some managers strive to maintain stable dividends during the crisis period. Nevertheless, their ability to do so weakens during this period.